Technology Use, Organisational Flexibility and Innovation: Evidence for Germany - Thomas Hempell; Thomas Zwick (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2005)
This paper investigates to what extent the usage of information and communication technology (ICT) fosters innovation activities by facilitating more flexible organisational structures in firms. We distinguish between functional flexibility (the ability of workers to co-operate and take decentralised decisions) and numerical flexibility (the reduction of fixed costs, mainly due to outsourcing business processes). Our results from a large and representative data set of firms in Germany show that ICT use is associated with an increase in both types of flexibility but the implications for innovation activities differ. Functional flexibility is strongly positively associated with product innovations. In contrast, numerical flexibility allows firms to ?buy? innovations in the short run, but reduces innovative capacity in the longer run.
Keywords: O31; L23; L22; 330; ICT usage; flexibility; innovations; Computergestütztes Verfahren; Informationstechnik; Reorganisation; Flexibilität; Innovation; Schätzung; Deutschland